The Embodied Teaching of Spatial Terms: Gestures Mapped to Morphemes Improve Learning - Janzen Ulbricht, Natasha (Frontiers in Education, 2020)
Learning spatial terms in a second language is often an arduous task which learners perform with varying levels of success. While classroom-based studies of gesture have shown the importance of embodied learning, predictions about which teaching gestures are most effective remain rare. In the context of learning and performing a play, this study investigates two English language teaching methods, one with teacher gestures at the level of morphology and one with gestures at the sentence level. This experiment with a diverse group of primary-school-age children from Germany and Poland (N = 76) shows that although over time both groups made similar gains in understanding and using spatial terms, this gain was more immediate for learners exposed to one gesture per morpheme. For beginning learners spatial terms are frequent, important and abstract, hence this research may have important implications for understanding the nature of effective methods for teaching and testing abstract concepts.